Water pollution potential and management strategies of UTM skudai food courts greywater system : A questionnaire – based study - Aiman Bin Ponniran, Muhammad; Zuhaili Bin Mohamed Najib, Mohamed (Environmental and Toxicology Management, 2023)
Rapid urbanisation and population expansion in Malaysia have resulted to both an ever need for water use and an increase in water pollution. Supply of water in general, as well as water quality, is a key challenge in Malaysia. Lakes and reservoirs serve as residential, commercial, agricultural, navigational, hydroelectric, and recreational water supplies. As rivers provide 98 percent of the world’s water, river pollution is a serious issue as more rivers get contaminated. This study is focusing on the public awareness on the potential of the greywater discharge from the café and laundry to the nearest river at UTM Skudai. Generally, about 64 sets of survey questionnaires were distributed to students and university personnel who commonly visit Arked Cengal. Arked Meranti and Arked Angkasa. Also there will be interview session with the stall workers to interview about the management of the greywater discharge.